PENGARUH TINGKAT UPAH, PRODUKSI, MODAL TERHADAP PENYERAPAN TENAGA KERJA PADA INDUSTRI BATIK DI KECAMATAN TANJUNG BUMI KABUPATEN BANGKALAN - ROHMAN, ABDUR; INGGIT, KUNTO (JEB17 : Jurnal Ekonomi dan Bisnis, 2019)
ABSTRACT  The role of the batik industry in particular can support national development. Labor absorption effort is inseparable from the factors – factors that affected it, such as the level of wages, production and capital issued. This study examined the influence of the level of wages, production, capital against labour absorption in the batik industry in Bangkalan Regency Tanjung Earth. With the intention of wanting to know if there was any influence between the level of wages, production, capital against labour absorption in the batik industry in Bangkalan Regency Tanjung of the Earth, in the hope it can be used as a basis in determining the policy in addressing the problem of employment in Bangkalan Regency. The data used in this research is the primary and secondary data are obtained from the results of a questionnaire that was distributed to the relevant parties as well as the Central Bureau of statistics (BPS) Bangkalan Regency Bangkalan Regency in numbers or 2017. Methods of analysis used in this study is a method of multiple regression analysis with the help of SPSS. The results of this research show that there are influences the level of wages, production, capital against labour absorption in the batik industry in Bangkalan Regency Tanjung Earth with the results showing that F F > tables to calculate and t > t table calculate and from the results of the calculation of the coefficient of determination of 0.937 obtained that the variable wage rate, production, capital together – the same can explain the variable absorption of labor amounted to 93.7%. Keyword: wage rate, production, capital, labour absorption in the batik industry in Bangkalan Regency Tanjung Earth